2021
DOI: 10.1371/journal.pone.0245955
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the long-acting regimen cabotegravir plus rilpivirine for the treatment of HIV-1 and its potential impact on adherence and viral transmission: A modelling study

Abstract: Introduction Combination antiretroviral therapy (cART) improves outcomes for people living with HIV (PLWH) but requires adherence to daily dosing. Suboptimal adherence results in reduced treatment effectiveness, increased costs, and greater risk of resistance and onwards transmission. Treatment with long-acting (LA), injection-based ART administered by healthcare professionals (directly observed therapy (DOT)) eliminates the need for adherence to daily dosing and may improve clinical outcomes. This study repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…A modelling study from Canada concluded that, based on better adherence driving higher rates of viral suppression and fewer onward transmissions, IM-CAB/RPV would yield cost-savings ($1.5 million lifetime savings per 1000 patients treated), life-year and quality adjusted life-year gains and 3 fewer transmissions than oral ART [15]. However, predicted adherence to IM-CAB/RPV was based on that observed in clinical trials, whereas adherence to oral ART was based on real-life Canadian cohorts, assumptions that may favour the IM-ART strategy.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…A modelling study from Canada concluded that, based on better adherence driving higher rates of viral suppression and fewer onward transmissions, IM-CAB/RPV would yield cost-savings ($1.5 million lifetime savings per 1000 patients treated), life-year and quality adjusted life-year gains and 3 fewer transmissions than oral ART [15]. However, predicted adherence to IM-CAB/RPV was based on that observed in clinical trials, whereas adherence to oral ART was based on real-life Canadian cohorts, assumptions that may favour the IM-ART strategy.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…The cost of LAI ART and several first-line oral HIV medications is comparable [ 28 ]. According to the U.S. Department of Health and Human Services, the monthly average wholesale price of LAI cabotegravir/rilpivirine ranges from $4752 to $7218 depending on the dose, which amounts to $43,308 per year for bi-monthly injections or $57,024 per year for monthly injections (excluding oral lead-in and initiation injections).…”
Section: Policymentioning
confidence: 99%
“…Thus, as patents for oral HIV medications continue to expire, the cost differential between LAIs and oral medications will grow. Still, LAIs may remain cost-effective given greater beneficial impacts on adherence and viral suppression [28]. Because youth experience particular challenges adhering to ART for both treatment and prevention [31][32][33], cost analyses should estimate relative cost and benefits specific to young PWH.…”
Section: Costmentioning
confidence: 99%
“…A recent study in a sub-Saharan setting showed that CAB+RPV LA Q1M would be more cost-effective in PLHIV with suboptimal adherence; these results were also supported by a study in a US setting [ 18 , 19 ]. Additionally, a Canadian study demonstrated CAB+RPV LA Q1M to be the dominant intervention (more effective and less costly) compared with daily oral regimens [ 20 ]. Here, the cost-effectiveness of CAB+RPV LA Q2M compared with daily oral STRs was evaluated from the Spanish National Health System perspective.…”
Section: Introductionmentioning
confidence: 99%